Dampak Pola Asuh Otoriter terhadap Karakter dan Perkembangan Mental Anak - Oktaviani Herlina; Zahira Nisrina Huwaida; Pramestti Ni Kadek Ayu Regita (Jurnal Gesi, 2023)
Parenting is an interaction that exists between parents and their children. Parenting that is applied dailyplays a very important role in shaping the character of children. Parenting in which it applies that childrenmust obey all the orders of their parents is called authoritarian parenting style. This study aims to determinethe relationship between authoritarian parenting on the character and mental development of children. Thesubject of this study was a child who was raised with an authoritarian parenting style as many as 26 people.This research uses survey methods and literature study. The purpose of distributing this questionnaire is toobtain and collect opinions from the respondents which can then be used as primary data. The literaturestudy method is a method by analyzing and studying other references on the topics discussed to strengthenresearch data. The results of this study indicate that there is a large influence between authoritarianparenting and the character and mental development of children.Kata kunci : Authoritarian Parenting Style, Character, Children's Mental Development